PENGEMBANGAN SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN DAN PENCARIAN LOKASI USAHA KERAJINAN TANGAN MENGGUNAKAN CAKEP HP - Pratama, Meireza; Sholeh, Mohammad; Widyastuti, Naniek (Jurnal Script, 2015)
ABSTRACTHandicraft businesses is one of the businesses in Yogyakarta. The presence of GIS-based information system that would be very helpful to present information that is complete, and make the guide / tool to search for reaching these businesses to craft intended to integrate the map route or Jogja as a hint to go to the handicraft businesses. The system is built using web-based programming using CakePHP, with a MySQL database. Features map in this study using the Google Map API. Google map also has support for the manufacture of Yogyakarta which will be integrated with the location of handicrafts. The Geographic Information System has a feature to search information of handicrafts, handicraft businesses, location search, the route to the search of handicrafts using the instructions map, in this system there are also related products on the existing handicraft businesses. Using Geographic Information System handicraft businesses is expected to greatly assist visitors in finding a variety of handicrafts information in Yogyakarta.Â Keywords : GIS, Business Crafts, Routes, Google Map.